Corpo e sexualidade: discursos constituidores nas revistas Nova e Playboy anos 1970 - Mucelin, Patrícia Carla (2013)
This research has as it s source and object the New Cosmopolitan and Playboy Magazines from 1970s. Sought to analysis through a qualitative study of the Nova's and Playboy's speeches about beauty, sensuality, sexuality and behavior to understand how these two magazines gave meaning to gender identities. The discourse analysis was performed based on the categories gender and identities, to understand how were build the masculine and feminine identities and how the power relationships between genders has occurred, noticeable in the Articles, covers and summaries of the two magazines. The Nova Cosmopolitan s writing to single women who were entering into the labor market, therefore the magazine sought to show that maintain a lasting relationship with a steady partner and build a carrier were synonymous of achievement, and both, taught how women should take care of the beauty and follow conduct rules in their relationships. The Playboy turned to single men that seek pleasure as a lifestyle, showed in it s columns information about sex and relationships and how men could turn around their insecurities to conquer women. The sensuality was the most valued characteristic by both magazines, to constitute the idealized images of feminine and masculine body